A Mixed-Methods Study of Patient–Provider E-Mail Content in a Safety-Net Setting. Issue 1 (2nd January 2016) - Mirsky, Jacob B.; Tieu, Lina; Lyles, Courtney; Sarkar, Urmimala
Abstract : To explore the content of patient–provider e-mails in a safety-net primary care clinic, we conducted a content analysis using inductive and deductive coding of e-mail exchanges ( n  = 31) collected from January through November 2013. Participants were English-speaking adult patients with a chronic condition (or their caregivers) cared for at a single publicly funded general internal medicine clinic and their primary care providers (attending general internist physicians, clinical fellows, internal medicine residents, and nurse practitioners). All e-mails were nonurgent. Patients included a medical update in 19% of all e-mails. Patients requested action in 77% of e-mails, and the most common requests overall were for action regarding medications or treatment (29%). Requests for information were less common (45% of e-mails). Patient requests ( n  = 56) were resolved in 84% of e-mail exchanges, resulting in 63 actions. These results show that patients in safety-net clinics are capable of safely and effectively using electronic messaging for between-visit communication with providers. Safety-net systems should implement electronic communications tools as soon as possible to increase health care access and enhance patients' involvement in their care.